Ethics and Compliance in Drafting Business Contract Agreements - Santoso, Mulyani (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
Ethics and compliance are fundamental to the quality of business contract drafting and implementation. This article maps the relationship between ethical principles (honesty, transparency, responsibility, fairness) and Indonesia's legal compliance framework (the Civil Code, the Electronic Information and Transactions Law, and Government Regulation No. 71/2019 on Electronic Systems and Transactions, and the Financial Services Authority (OJK) governance regulations), while integrating research findings and current practices (OECD 2024–2025; World Bank 2023–2024; SNI ISO 37001:2016 standard). The analysis demonstrates that ethical and compliant contracts are not only valid and legally binding but also strengthen governance, reduce the risk of disputes, increase stakeholder trust, and support supply chain sustainability. The article offers a practical framework for principles-based contract drafting that aligns with legal, governance, anti-corruption, and sustainability due diligence requirements. Recommendations focus on the integration of ethics clauses, language compliance testing and certified electronic signatures, integrity risk assessments, and a measurable contract management plan. These findings are relevant to business actors, legal advisors, regulators, and compliance auditors.